2010
DOI: 10.1002/jbm.b.31691
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration: Dynamic procedures versus static shielding in an animal model

Abstract: Due to its osteoinductive potential, the periosteum plays a crucial role in the process of neoosteogenesis. Therefore, periosteal elevation can lead to new bone formation in an artificially created space. In this study, we compared dynamic periosteal elevation with static shielding in an animal experiment. Different elevation/shielding heights of 5, 10, and 15 mm were tested with regard to various consolidation periods. Histological analysis, histomorphometry, and microradiography were used to measure the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
(28 reference statements)
3
22
2
Order By: Relevance
“…It seems that bone regeneration was induced by the gradual expanding force of the elasticity of the SMA device. Lethaus et al showed that the newly formed bone in the static periosteal shielding procedure was almost the same as that in the dynamic periosteal elevating procedure 15. This is different than the present results.…”
Section: Discussioncontrasting
confidence: 92%
“…It seems that bone regeneration was induced by the gradual expanding force of the elasticity of the SMA device. Lethaus et al showed that the newly formed bone in the static periosteal shielding procedure was almost the same as that in the dynamic periosteal elevating procedure 15. This is different than the present results.…”
Section: Discussioncontrasting
confidence: 92%
“…No significant difference was seen between static and dynamic periosteal elevation with regard to the degree of mineralization, trabecular architecture and bone density on the calvaria of minipigs. 22,23 New bone would possibly be more calcified by decortication of the original bone. 17 This was, however, not performed as it might have overridden the effect of the periosteum stimulation alone.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the conventional DO, the distraction cavity is bordered by the original surface of the bone base and the periosteal (i.e., cambial) layer when a gradual distraction of the periosteum is applied. By application of perforated distraction plates or meshes in different models of periosteal distraction osteogenesis (PDO), new bone was formed to varying extents 9‐17 . Sencimen et al 18 found significant differences in the extent of newly formed bone between conventional DO and PDO disclosed by high content of interstitial fatty tissue.…”
mentioning
confidence: 99%